2019
DOI: 10.21451/1984-3143-ar2018-0127
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction: screening and diagnosis using animal models

Abstract: Intrauterine growth restriction (IUGR) is a serious condition of multifactorial origin, mainly caused by maternal malnutrition, multiple gestation associated with nutrient competition, abuse of nocive substances and infections. The diagnosis of such syndrome is complex, as its own manifestations can mask its occurrence, requiring a thorough assessment of body weight and size. Moreover, it is not responsive to any kind of treatment. There is evidence that IUGR may predispose the individual to several pathologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
3
3
0
Order By: Relevance
“…This measurement reflects fetal growth and development, and the observed decrease suggests that caffeine exposure may hinder fetal growth. This finding is consistent with previous studies linking caffeine intake to impaired fetal growth (Lunde et al, 2016;Felicioni et al, 2019). Changes in the major and minor axes can indicate abnormalities or disruptions in placental growth and morphology, which can impact fetal health and development.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This measurement reflects fetal growth and development, and the observed decrease suggests that caffeine exposure may hinder fetal growth. This finding is consistent with previous studies linking caffeine intake to impaired fetal growth (Lunde et al, 2016;Felicioni et al, 2019). Changes in the major and minor axes can indicate abnormalities or disruptions in placental growth and morphology, which can impact fetal health and development.…”
Section: Resultssupporting
confidence: 92%
“…This ratio is a crucial indicator of placental efficiency, and the observed changes in this study suggest that caffeine interferes with placental function, potentially leading to nutrient insufficiency for the developing fetus. This is consistent with previous studies emphasizing the impact of caffeine on placental efficiency and fetal nutrition (Felicioni et al, 2019;Qian et al, 2020). Crown-rump length is a measurement commonly used to estimate fetal age and assess fetal growth and development during pregnancy.…”
Section: Resultssupporting
confidence: 92%
“…Exposure to a low-protein diet (LPD) during gestation in rodents is a recognized preclinical model to induce IUGR and its developmental consequences on the immature brain [22,23]. Animals exposed to an antenatal LPD are characterized by brain alterations, including defective myelination and abnormal brain connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Infants affected by IUGR are born SGA. However, some children born SGA are not IUGR, but rather just genetically small 181 . Infants born SGA often show signs of catch-up growth 182 and studies have shown that this elevates the risk for obesity later in life 180 .…”
Section: Explanatory Hypothesesmentioning
confidence: 99%